La maîtrise des populations de grands ongulés dans les espaces naturels protégés : comment gérer la spatialité animale par des territoires humains ? - Yves Poinsot; François Saldaqui (Cybergeo, 2012)
The protected natural spaces where endangered species and ecosystems are preserved, shelter high populations of tall ongulated. These numerous animals present a risk for the scarce species and they increase agricultural and pastoral damages on the outskirts. The Cévennes national park is compelled by this phenomenon to practice regulating shootings in central areas. In winter, in the Spanish park of Aigues Tortes, because of the snow in high altitudes, animals are forced to progress outside the park limits where a common cynegetic regulation takes place. The elimination of some wild boars within the national park of Occidental Pyrenees could have helped to save bears while reducing beats in the closest periphery. The necessary regulation in the central zone implies to look for the actors of this management. The functionaries, too rare, could be helped by hunters holding a specific hunting license for whom they would manage areas, dates and conditions of intervention.The presence of the wolf may become an alternative. Its trophic and territorial behavior makes him efficient against animals of easy capture (moufflon or even cervid). The pressure on wild boars is significant only with high density of wolves. In that case, the pressure on domestic ongulated living in protected areas increases significantly and involves unbearable breeding conditions in periphery. To the binary opposition between sanctuaries and unprotected areas could succeed a gradation of more elaborated statuses. It leads to call into question our mental or cartographic representations of labelled areas..